2021
DOI: 10.2147/idr.s299704
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting the Tuberculosis Incidence Using a Novel Ensemble Empirical Mode Decomposition-Based Data-Driven Hybrid Model in Tibet, China

Abstract: The purpose of this study is to develop a novel data-driven hybrid model by fusing ensemble empirical mode decomposition (EEMD), seasonal autoregressive integrated moving average (SARIMA), with nonlinear autoregressive artificial neural network (NARNN), called EEMD-ARIMA-NARNN model, to assess and forecast the epidemic patterns of TB in Tibet. Methods: The TB incidence from January 2006 to December 2017 was obtained, and then the time series was partitioned into training subsamples (from January 2006 to Decemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 59 publications
(112 reference statements)
0
5
0
Order By: Relevance
“…They concluded that by using the appropriate methods that are suitable to the data, one can achieve consistent results in modelling and predicting any series of an epidemic. For more epidemic hybrid time series forecasting, see, for example, 34 42 .…”
Section: Literature Reviews and Related Workmentioning
confidence: 99%
“…They concluded that by using the appropriate methods that are suitable to the data, one can achieve consistent results in modelling and predicting any series of an epidemic. For more epidemic hybrid time series forecasting, see, for example, 34 42 .…”
Section: Literature Reviews and Related Workmentioning
confidence: 99%
“…It can be said that this data-driven mixture technique shows a strong capacity to improve the forecasting power for the prevalence and mortality data of COVID-19 in that the principal advantage of such a model facilitates to identify the preferred hybridization by decomposing the target data into various multi-scale levels to consider the underlying trend and random parts simultaneously by use of the different types of models. Given the forecasting superiority of our proposed data-driven hybrid method, it seems that this hybrid model is also useful in nowcasting and forecasting the epidemiological trends of the COVID-19 prevalence and mortality time series in other regions or other infectious diseases 44 . Of note, current studies found that some other forecasting tools (e.g., the new innovations state space modeling framework 59 , long short-term memory neural network 60 , advanced error-trend-seasonal (ETS) framework 61 , α-Sutte Indicator 62 , and SBDiEM 30 ) performed a highly accurate forecast for the epidemiological trends of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…However, the above-referenced models are only a simple ensemble architecture comprising either a basic linear or nonlinear model based on the EEMD technique, which is unable to consider both linear and nonlinear components in a time series simultaneously despite a performance improvement over the basic models by use of these ensemble architectures. Motivated by the “decomposition and ensemble” idea based on the EEMD method, a promising alternative is to develop an ensemble architecture by integrating the linear trait with the nonlinear trait decomposed by the EEMD method using an adequate linear model and nonlinear model 44 . By doing so, this new ensemble architecture is capable of capturing both components in a time series simultaneously.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Our estimated reductions in the TB morbidity are becoming slow, this is aligned with some earlier reports, 1,2,33 which also signals a slow falling or a recurring risk in the TB morbidity in some countries in recent years because of climate change, large-scale population migration, increasing drug-resistant TB, under-nutrition, co-infection with HIV, alcohol use disorders, smoking, together with the comorbid conditions of diabetes and hypertension. 2,43 Accordingly, to ensure that China is on track to reach the WHO's End TB Strategy, some additional technological breakthroughs that can substantially reduce the risk of developing TB among the susceptible population and comprehensive interventions (eg, optimization of the current prevention measures and the development of an effective post-exposure vaccine or a short, efficacious and safe treatment for TB infection 2,43 ) are required.…”
mentioning
confidence: 99%